Factors associated with the lethality of human leptospirosis in Brazil - Alice Nardoni Marteli; Laurindo Antonio Guasselli; Décio Diament; Daniel Savignon Marinho; Geraldo Marcelo da Cunha; Federico Costa (Cadernos de Saúde Pública)
Human infection by Leptospira results from direct exposure or indirect contact with soil or water contaminated by the urine of carrier mammals. Despite the current knowledge about the modes of infection, there are still gaps in understanding the factors that contribute to the disease lethality. Aiming to identify factors associated with death from leptospirosis in Brazil, a retrospective exploratory cross-sectional study was conducted using data from the Brazilian Information System for Notificable Diseases of the Brazilian Ministry of Health, from 2007 to 2019. From an initial total of 50,640 confirmed cases, 38,206 (75.45%) cases were selected for analysis, of which 10.39% (3,968) represented deaths. Among the sociodemographic factors associated with death from leptospirosis, notable ones included contact with trash/rubble, work-related infection, male gender, non-white skin color, and increased risk with age. Among the clinical factors, notable ones included the presence of respiratory alterations, clinical-epidemiological confirmation criteria, pulmonary hemorrhage, kidney failure, jaundice, cardiac alterations, and vomiting. Regarding geographical distribution, residing in the Southeast increased the chance of death by 83% compared to individuals residing in the North, which had the lowest proportion of deaths (5.68%). The results found in this study provide an overview of the lethality of leptospirosis in humans in Brazil. Regional differences should be better investigated to guide health policies.